Effects of Dietary Regimens and Brown-Egg Pullet Strain on Growth and Development - Anderson, K.E. (International Journal of Poultry Science, 2010)
This study consisted of; two strains of brown-egg pullets, the Hy-Line (HB) and H&N (BN) Brown were raised on three different dietary regimens resulting in a 2 x 3 factorial design. The three different regimens were a standard Step-down Protein Regimen (SDP) comprised of a 20% CP Starter, 0-6 week, 18% CP Grower 1, 7-12 week and 16% CP Grower 2, 13-18 week; a Step-up Protein Regimen (SUP9) comprised of a 12% CP Starter, 0-9 week, 16% CP Grower 2, 10-16 week and 18% CP Grower 1, 17-18 week and a Step-up Protein Regimen (SUP12) comprised of a 12% CP Starter, 0-12 week, 16% CP Grower 2, 13-16 week and 18% CP Grower 1, 17-18 week. The pullets were housed in an environmentally controlled rearing facility with trideck battery cages. Feed consumption and body weights were measured bi-weekly and mortality was recorded daily. At 17 week of age a sample of 20 pullets from each strain and regimen combination were randomly selected and brought to the laboratory for body composition analysis. At 18 week the HB and BN strains only differed in livability with the HB having a 4.2% greater (p